2020
DOI: 10.1177/0363546520913528
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Meniscal Scaffold for the Treatment of Partial Meniscal Deficiency: 5-Year Follow-up Outcomes: A European Multicentric Study

Abstract: Background: A biodegradable polyurethane scaffold was developed to treat patients with the challenging clinical condition of painful partial meniscal defects. Hypothesis: The use of an acellular polyurethane scaffold in patients with symptomatic partial meniscal defects would result in both midterm pain relief and improved function. Study Design: Case series; Level of evidence, 4. Methods: A total of 155 patients with symptomatic partial meniscal defects (101 medial and 54 lateral) were implanted with a polyur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…A comparison with the results of other scaffolds for lateral meniscus is possible only for the polyurethane scaffold (ACTIfit) at 5 years of follow-up 21 ; the reported survival rate (86.9%) is similar to the 85% rate reported during the same time frame in the present study. In contrast, the mean KOOS and VAS values of ACTIfit at 5 years appear to be slightly higher than the values reported for the CMI at 10 years.…”
Section: Discussionsupporting
confidence: 82%
“…A comparison with the results of other scaffolds for lateral meniscus is possible only for the polyurethane scaffold (ACTIfit) at 5 years of follow-up 21 ; the reported survival rate (86.9%) is similar to the 85% rate reported during the same time frame in the present study. In contrast, the mean KOOS and VAS values of ACTIfit at 5 years appear to be slightly higher than the values reported for the CMI at 10 years.…”
Section: Discussionsupporting
confidence: 82%
“… 5 , 6 , 7 Meniscectomies are a primary risk factor for knee osteoarthritis, 8 , 9 , 10 , 11 , 12 , 13 which led to efforts toward developing solutions to preserve or restore as much meniscal tissue as possible. 14 , 15 , 16 , 17 , 18 Unfortunately, surgical intervention is not always avoidable, and arthroscopic isolated meniscectomy (AM) remains one of the most commonly performed orthopedic procedures. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Initial studies analyzing tissue ingrowth into the scaffold showed vital cells on histological examination and complete integration on second look arthroscopy in 97.7% of the cases at 12 months follow-up. 10 Recent studies with long-term followup 11,12 had demonstrated that the polyurethane meniscal implant was able to improve knee joint function and reduce pain in patients with segmental meniscal deficiency over 5 years after implantation with high survival rates that are comparable to meniscal allograft transplantation after total meniscectomy. Despite these favorable results, concerns still exist regarding the biologic response needed to achieve the goal of establishing a biomechanically functioning meniscus or provide an equivalent meniscus substitute.…”
Section: Introductionmentioning
confidence: 99%